2000
DOI: 10.1177/00220345000790040801
|View full text |Cite
|
Sign up to set email alerts
|

Pellicle Precursor Protein Crosslinking: Characterization of an Adduct between Acidic Proline-rich Protein (PRP-1) and Statherin Generated by Transglutaminase

Abstract: Recent work with oral transglutaminase indicated that this enzyme, derived from oral epithelial cells, crosslinked pellicle precursor proteins which may be important in the formation of the acquired enamel pellicle. The purpose of this study was to investigate whether purified acidic PRP-1 can form crosslinks with statherin, and whether such a crosslink is derived from a transglutaminase-catalyzed reaction between glutaminyl and lysyl side-chains, leading to a covalent bond formation. Enzymatic reaction produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Moreover, in the guanidine extract three phosphorylated peptides were detected while a much higher number of these species (n = 9) were observable on the TFA fraction (identified as fragments i 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.jss-journal.com of statherin, acidic PRPs, collagen and basic salivary proline-rich protein 4 allele L). The ability of statherin and of acidic PRPs to adsorb to enamel surface has been extensively described [5,13,21,23,28,30]. Most of the identified species in this work were fragments and were resultant of the degradation from intact species that are also present on AEP.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, in the guanidine extract three phosphorylated peptides were detected while a much higher number of these species (n = 9) were observable on the TFA fraction (identified as fragments i 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.jss-journal.com of statherin, acidic PRPs, collagen and basic salivary proline-rich protein 4 allele L). The ability of statherin and of acidic PRPs to adsorb to enamel surface has been extensively described [5,13,21,23,28,30]. Most of the identified species in this work were fragments and were resultant of the degradation from intact species that are also present on AEP.…”
Section: Discussionmentioning
confidence: 75%
“…Within 30 min, the thickness layer of the biofilm increases, most probably, by the adsorption of other proteins through protein -protein interaction, forming globular structures usually assigned as micelle-like structures [10,11]. Enamel acquired pellicle formation is a dynamic process since, under in vivo conditions, the enamel surface is continuously exposed to whole saliva with new species, its inherent proteolytic activity [12] and to enzymatic crosslinking (mainly via transglutaminase activity) [13,14]. This exposure leads to time course modifications of the adsorbed species with the presence of unique molecular forms.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that proteins originating from non-glandular sources may contribute more significantly to WS and EP than previously recognized or that proteins may have undergone extensive proteolysis, cross-linking, and other modifications (54,55). Some interesting contributors to EP are members of the cytokeratin family, cytokeratin 13 and 15 (56), pointing to oral epithelium as one of the sources of proteins deposited on the tooth surface.…”
Section: Fig 2 Two-dimensional Gel Electrophoresis Of Salivary Glanmentioning
confidence: 88%
“…Tissue samples used for ISH and IHC were thawed on ice, fixed in 4% paraformaldehyde at 4C overnight, embedded in paraffin, sectioned, and mounted on microscope slides. Buccal epithelial cells were obtained from whole saliva sediment as described (Yao et al 2000). These studies were approved by the Institutional Review Board at Boston University Medical Center.…”
Section: Tissue Samplesmentioning
confidence: 99%